O ser em cena: afásico e cuidador no cenário da vida - Monje, Regina Yara Pereira Rondon (2007)
This paper is an investigative study based on the use of the quantitative and qualitative methodologies with the objective of evaluating the quality of life of the aphasic citizen and its care taker, who participate of the ONG Ser em Cena . The methodologies are mutually complementary pointing out the perspective of the centrality and the respect to the citizens, offering elements that contribute in such a way for the implementation of proposals of action in the Ser em Cena , and in the Politics of Health that in fact propitiate the autonomy and the life quality improvement of the aphasic person and care taker. In the quantitative stage we applied for the two groups of citizens the generic questionnaire of evaluation of life quality - World Health Avality Organization of Life - shortened, WHOQOL-BREF in Portuguese version. The quantitative data were gotten by verbal statement, to the light of the Verbal History methodology, which were recorded in an interview situation with the usage of a script of specific questions for the aphasic person and the care taker. In the research 11 aphasic people and 9 care takers participated as citizens; from these participants, 2 aphasic people are independent and live by themselves. The statements collected disclose the obstacles of the aphasia, but also they disclose the forms of facing these obstacles. It shows the necessity of looking at the aphasic person not only for its problem of communication, but looking at the aphasia in a global way. The rehabilitation model goes beyond the recovery of the language; it must be extended to the other dimensions of the life that were also reached